Intra and Extracellular Protein Interactions with Tau - Hernandez, F.; Avila, J. (Current Alzheimer Research, 2010)
Tau is a sticky protein mainly expressed by neurons, which may be found in different subcellular fractions or outside the cell. Tau is mainly associated to microtubules in the cytoplasm, although besides tubulin, tau can also bind to other proteins and to itself to form different polymers, some of which are relevant in pathological disorders. In this short review, we have revised some of the interactions involving tau, both inside or outside of the cell. Different regions of tau are involved in these interactions and some of them are more conserved throughout evolution than others.
Keywords: extracellular tau protein